ANALISIS MANAJEMEN ASET DAERAH DALAM PENINGKATAN PENDAPATAN ASLI DAERAH DI KABUPATEN LAMONGAN (Studi Tentang Aset Tetap Berwujud Objek Wisata Daerah) - Risambessy, Richard Izaac (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2009)
The aim of this research is to discover and analyze: (1) The influence of district assets controlling system to the empowerment of district assets; (2) The influence of district asset accounting to the empowerment of district assets; (3) The influence of district’s asset empowerment to the performance of district assets; (4) The influence of the district assets performance to the district’s genuine revenue; (5) The influence of district assets accounting to the district assets controlling system; (6) The influence of district assets controlling system to the district asset performance; (7) The influence of district assets accounting to the districts asset performance; (8) The influence of district asset controlling system to the district genuine revenue; (9) The influence of district asset accounting system to the district genuine revenue.The results of the research conducted, discovered that: 1). District asset controlling system has significant positive influence to the empowerment of district asset; 2) District asset accounting system has non significant positive influence to the empowerment of district asset; 3) The empowerment of district asset has non significant positive influence to the districts asset performance; 4) The performance of district asset has significant positive influence to the district’s genuine revenue; 5) District asset accounting has significant positive influence to district asset controlling system; 6) District asset controlling system has non significant positive influence to district asset performance; 7) District asset accounting system has non significant positive influence to the district asset performance; 8) District asset controlling system has non significant positive influence to district actual income; 9) accounting system of district asset has non significant positive influence to district actual income.Key words:      The Empowerment Of District Assets, Management Control Of District Assets, District Asset Accountancy, District Actual Income.